Intention To Purchase Via The Internet: A Comparison Of Two Theoretical Models - J. Ma'ruf, Jasman; Mohamad, Osman; T. Ramayah, T. Ramayah (Asian Academy of Management (AAM), 2005)
This study compares two models for predicting intention to purchase via the Internet. The behavioral intention to purchase via the Internet was examined as a function of attitude towards purchase, perceived usefulness, and perceived ease of use Technology Acceptance Model (TAM), or attitude towards purchase, subjective norm, and perceived risk (Theory of Planned Behavior [TPB]). Results indicate that both models significantly influenced behavioral intention to purchase. We compared both models, and found that TPB (adjusted R2 = 0.55) is better than TAM (0.44) in explaining behavioral intention to purchase (BI). After we integrated TAM and TPB, we found that perceived risk (β = –0.332) is the primary determinant of BI, with subjective norm (SN) (β = 0.210) as the significant secondary determinant, followed by attitude (A) towards purchase (β = 0.175), perceived usefulness (β = 0.159), and perceived ease of use (β = 0.069).